Pathological Risk Factors in Retinoblastoma Patients Underwent Enucleation - I Wayan Eka Sutyawan (Journal of Global Pharma Technology, 2016)
Objective: Retinoblastoma is a malignancy that originates from primitive retinal cells and is usually found in children under 4-5 years of age. Retinoblastoma is the second largest cause of death among other malignancies in developing countries. The purpose of this study was to determine the characteristics and pathological risk factors of enucleated retinoblastoma Patients and Methods: This is a descriptive study with a cross-sectional study design conducted retrospectively by evaluating data from the patient's medical record. A total of 18 subjects were enrolled in this study. Characteristics observed were sex, age, and laterality.  Data was compiled and calculated by Microsoft Excel 2017 software. All calculations and presentations were conducted in descriptive manner. Results: Unilateral retinoblastoma cases (77.2%) were found more often in this study. Leucochoria was the most often presenting symptoms (61.1%), followed by propotosis, strabismus, and cellulitis. Out of 18 subjects, 72.2% subjects had intraocular retinoblastoma. The most common PRF finding in this study was optic nerve invasion (44.4%), followed by choroid invasion, and scleral invasion. While 11.1 % of the subjects had no PRF findings. Conclusion: Invasion to the optic nerve was the most common pathological risk factors found in enucleated retinoblastoma. Other PRFs include choroid invasion and sclera invasion. PRFs may become a sign that determines the progressivity of retinoblastoma, and it can also determine further decisions regarding the prevention of recurrence and possible adjuvant therapy in retinoblastoma patients.Keywords: Pathological risk factor, Retinoblastoma, Enucleation.